Evaluation and characterization of the bioactive compounds of camu-camu (Myrciaria dubia (H.B.K) Mc Vaugh) : Avaliação e caracterização dos compostos bioativos do camu-camu (Myrciaria dubia (H.B.K) Mc Vaugh) - Cunha, Elenice Carla Emidio, 1986- (2018)
Orientador: Helena Teixeira Godoy